Interferometric 3mm spectral line and continuum survey of the central molecular zone. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Pound, Marc W.; Yusef-Zadeh, Farhad
Abstract: Because of its large angular extent, the central molecular zone (CMZ) has to date only been mapped in the mm with single dish telescopes, with resolution about 30″ (1.4 pc). We present the first interferometric maps of a 90 × 50 pc region of the CMZ, with spatial resolution of ∼10″ (0.4 pc). We mapped ∼0.25 square degrees of the CMZ with CARMA in 3mm continuum and the spectral lines SiO J = (2 − 1), HCO + J = (1 − 0), HCN J = (1 − 0), N2 H + J = (1 − 0), and CS J = (2 − 1), covering roughly VLSR = −200 to 200 km s −1 with spectral resolution ΔV ∼ 2.5 km s −1 . To recover the large scale structure resolved out by the interferometer, the continuum-subtracted spectral line images were combined with the Mopra 22-m telescope survey.